Time course of recovery of different motor functions following a reproducible cortical infarction in non-human primates - Kosugi, Akito; Saga, Yosuke; Kudo, Moeko; Koizumi, Masashi; Umeda, Tatsuya; Seki, Kazuhiko (Frontiers in Neurology, 2023)
A major challenge in human stroke research is interpatient variability in the extent of sensorimotor deficits and determining the time course of recovery following stroke. Although the relationship between the extent of the lesion and the degree of sensorimotor deficits is well established, the factors determining the speed of recovery remain uncertain. To test these experimentally, we created a cortical lesion over the motor cortex using a reproducible approach in four common marmosets, and characterized the time course of recovery by systematically applying several behavioral tests before and up to 8 weeks after creation of the lesion. Evaluation of in-cage behavior and reach-to-grasp movement revealed consistent motor impairments across the animals. In particular, performance in reaching and grasping movements continued to deteriorate until 4 weeks after creation of the lesion. We also found consistent time courses of recovery across animals for in-cage and grasping movements. For example, in all animals, the score for in-cage behaviors showed full recovery at 3 weeks after creation of the lesion, and the performance of grasping movement partially recovered from 4 to 8 weeks. In addition, we observed longer time courses of recovery for reaching movement, which may rely more on cortically initiated control in this species. These results suggest that different recovery speeds for each movement could be influenced by what extent the cortical control is required to properly execute each movement.